Observation of flux-creep in direction opposite to the Lorentz force. (24th February 2017) - Sawh, R-P; Weinstein, R; Carpenter, K; Parks, D; Davey, K
Abstract: The conclusion that free fluxoids move in the direction of F ⃑ = J ⃑ c × B ⃑ is broadly accepted. For certain spatial distributions of flux in HTS bulks, this requires free fluxoids to collect at the center of the bulk. Here, we report experiments in which such spatial distributions are created by means of zero-field-cool partial magnetization of the bulk, and the temporal changes in flux are measured. We report that the direction of the flux creep is observed to be opposite to F ⃑ = J ⃑ c × B . ⃑